MENENGOK PRIMADONA DAGANG PELABUHAN KUPANG, 1850-1870 - Fadliani Sahaka (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
Trade through the port of Kupang grew significantly after the port opened by the colonial government to be an international port at the beginning of the 19th century. The port served as a collecting center for smaller surrounding ports as well as for its hinterland. From the port of Kupang all export and import commodities could be traded. Between 1850-1870 the overall value of export and import fluctuated. The fluctuation was due to the fluctuating values of some the main commodities such as cloth, firearms, liquer and others. This paper also conclude that trade in the port of Kupang was dominated by Dutch-flag ships. In each period 90% of export and import values were carried by ships with Dutch flags while the remaining 10% with British and other ships.